Introduction to Flood Disaster Mitigation for Early Childhood through Digital Media Learning Videos in 2023 - Arif, Dimas Taufiq; Bachtiar, Rizky (Faculty of Civil Engeneering and Planning - ITATS, 2023)
Flooding is a natural hazard that occurs frequently in many locations in Indonesia. Flood catastrophe mitigation must be completed as a preventative measure before the disaster occurs. Flood disaster knowledge is an important learning activity for youngsters. Children can learn about flood catastrophe mitigation activities by using digital video as a learning medium. The lack of flood mitigation learning for children aged 5–6 years, as well as the children's lack of understanding of catastrophe mitigation, motivated this study. This study's data was gathered through interviews and questionnaires. The subjects of this study were five Kindergarten B students from Surabaya. The participants in this study were five Kindergarten B students from Surabaya. The study's findings indicate that digital media in the form of video can be used as a learning tool to teach early childhood flood catastrophe management. By watching digital educational video media, children are becoming more familiar with flood disasters and associated risk factors. The construction of a flood disaster management program in the form of digital instructional video media has been shown to boost early childhood knowledge and attitudes toward disaster response.